HRM 4. 0 for Human-Centered Organizations - Bissola, Rita (Advanced Series in Management Ser., 2019)
Offering researchers and professionals cutting-edge research and practical guidelines to turn the challenging scenario of Industry 4.0 into a successful transformation for the HRM domain, this volume focuses on three critical insights: HRM in the 4.0 era, job design for the smart economy, and HRM tools for digital transformation.